1999
DOI: 10.3109/03093649909071613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bending stiffness of six different colours of copolymer polypropylene

Abstract: This paper compares the bending stiffness of 5 different colours of copolymer polypropylene (CCP) with that of natural copolymer polypropylene (NCP). Flesh coloured and natural sheets are supplied thicker than other pigmented sheet. The bending stiffness of a specimen may be defined as EI, i.e. the product of E, Young's modulus of elasticity and I, the 2nd moment of area. Strips of “as supplied” (AS) and “post-draped” (PD) specimen were clamped and subjected to bending to assess the effect of pigmentation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…68 It was near this time that Prosthetics and Orthotics International published a related analysis of the bending stiffness of six different colors of copolymer polypropylene. 69 The authors described that pigmentation of copolymer altered its innate bending stiffness, but subsequently found that the variability in wall thickness inherent to drape forming appeared to negate the impact of such variability in the ultimate biomechanical performance of the device. 69 As the behavior of plastic was increasingly understood, the effect of both supplementary and replacement materials began to be explored.…”
Section: Applying Materials Properties To Orthosesmentioning
confidence: 99%
See 1 more Smart Citation
“…68 It was near this time that Prosthetics and Orthotics International published a related analysis of the bending stiffness of six different colors of copolymer polypropylene. 69 The authors described that pigmentation of copolymer altered its innate bending stiffness, but subsequently found that the variability in wall thickness inherent to drape forming appeared to negate the impact of such variability in the ultimate biomechanical performance of the device. 69 As the behavior of plastic was increasingly understood, the effect of both supplementary and replacement materials began to be explored.…”
Section: Applying Materials Properties To Orthosesmentioning
confidence: 99%
“…69 The authors described that pigmentation of copolymer altered its innate bending stiffness, but subsequently found that the variability in wall thickness inherent to drape forming appeared to negate the impact of such variability in the ultimate biomechanical performance of the device. 69 As the behavior of plastic was increasingly understood, the effect of both supplementary and replacement materials began to be explored. For example, Major et al 70 reported upon the resistance to dorsiflexion observed with four variations of the polypropylene AFO.…”
Section: Applying Materials Properties To Orthosesmentioning
confidence: 99%
“…Bench analyses have been conducted to investigate the torque-angle or torque-deflection relationships using a tension meter, [13][14][15][16][17] a strain gauge, 18 a load cell, 19,20 a dial gauge, [21][22][23] a forceplate, 24 or a muscle training machine. 25 Methods used to apply force to an AFO in previous bench studies have been generally grouped into two types, either direct application of force to a specific area of an AFO 13,16,22 or indirect application of force via a surrogate shank. 14,15,17,18,20,21,23 The advantage of conducting bench analyses is it is easier to control the experimental parameters in comparison to functional investigations.…”
Section: Introductionmentioning
confidence: 99%
“…However manual operation would induce a human error. The use of a load cell 19,20 and a dial gauge [21][22][23] would enable objective measurement of the stiffness of an AAFO. However, previous devices reported in the literature were primarily designed to test a non-articulated AFO (NAFO) [19][20][21][22][23] or require drill holes to bolt an AFO to the device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation